A novel, eco-friendly bio-nanocomposite (Alg-Cst/Kal) for the adsorptive removal of crystal violet dye from its aqueous solutions. Issue 8 (3rd July 2022) - Mittal, Jyoti; Ahmad, Rais; Ejaz, Mohammad Osama; Mariyam, Asna; Mittal, Alok
Abstract: Herein, we report the synthesis of a novel bio-nanocomposite (Alg-Cst/Kal) for the effective removal of the dye "Crystal Violet" from its aqueous solutions. In order to observe the surface morphology and functional groups, the bio-nanocomposite was characterized using various techniques such as SEM, EDX, TEM, FTIR, XRD, and TGA. The effect of parameters like contact time, pH, concentration and temperature on the adsorption of the dye over adsorbent has been studied in detail. The dye – adsorbent system has been tested over various isotherm models and found to follow the Freundlich adsorption isotherm model at 303 K. The developed bio-nanocomposite material exhibits an excellent adsorption toward Crystal Violet with a maximum adsorption capacity of 169.49 mg.g −1 . The experimental data has been further validated by applying various kinetic models and the pseudo-second order kinetic model was the best suited model. The calculated rate constant values ranged from 0.0046 to 0.0204 g.mg −1 .min −1 for different dye concentrations. The positive values of change in enthalpy, ΔH° (9.765 kJ.mol −1 ) and change in entropy, ΔS° (0.0565 kJ.mol −1 .K −1 ) obtained through thermodynamic studies demonstrate the endothermic nature and spontaneity of the adsorption process, respectively. The adsorption capacity of the adsorbent for the removal of the Crystal Violet dye was also compared with other adsorbents and found maximum. Novelty statement A novel bio-nanocomposite is synthesized by modifying the biopolymer alginate, cysteine and mixing the clay, kaolinite (Kal). The adsorption abilities of the material was tested the on the cationic hazardous dye, Crystal Violet. The material is novel and no attempt has so far been made to examine its batch adsorption abilities to remove hazardous dyes from the wastewater. The results are highly encouraging as out of all the adsorbents tested so far highest adsorption of the dye is observed in the present studies.